2023
DOI: 10.18332/tid/156109
|View full text |Cite
|
Sign up to set email alerts
|

Changes in tobacco and e-cigarette consumption in Spanish university students during the COVID-19 lockdown: Identification of vulnerable groups

Abstract: INTRODUCTION The objective of this study was to determine the changes in tobacco consumption in Spanish university students during the lockdown in 2020, and to identify vulnerable groups based on gender, age, and living situation. METHODS This was a cross-sectional descriptive study. From a sample of 1540 Spanish university students, 19.9% (n=306; 77.6% women; mean age=30.9 years; SD=8.3) reported having consumed tobacco. The frequency and average daily consumption of cigarettes and electronic nicotine delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This retrospective cohort study identified living arrangements as a predictor of frequent alcohol consumption. Besides frequent alcohol consumption, previous studies showed that university students living away from home were more likely to have unhealthy lifestyle factors than those living with their family, including smoking 11 and obesity. 12 These findings strongly suggest that university students living away from home are potential targets for improving health literacy regarding alcohol consumption, smoking, obesity and so on.…”
Section: Discussionmentioning
confidence: 99%
“…This retrospective cohort study identified living arrangements as a predictor of frequent alcohol consumption. Besides frequent alcohol consumption, previous studies showed that university students living away from home were more likely to have unhealthy lifestyle factors than those living with their family, including smoking 11 and obesity. 12 These findings strongly suggest that university students living away from home are potential targets for improving health literacy regarding alcohol consumption, smoking, obesity and so on.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Arjona et al [ 38 ] concluded that 40.9% of Spanish university students have a low adherence to a Mediterranean diet that suggests a high consumption of fats and sugars. Regarding tobacco consumption, 19.9% of university students in Spain reported having consumed it in the last 6 months (20.2% women; 18.9% men) [ 39 ]. As Correa states [ 40 ], some variables such as gender and smoking environment have a significant association with tobacco consumption.…”
Section: Discussionmentioning
confidence: 99%